A FRESH APPRAISAL OF THE NEO-EVANGELICAL PROJECT OF CULTURAL ENGAGEMENT. - Strachan, Owen (Fides et historia, 2015)
The article comments on David R. Swartz's book "Moral Minority: The Evangelical Left in an Age of Conservatism." It examines the vision, strategy, and cultural engagement practiced by the evangelical left from the 1960s to the 2000s in the U.S. It also criticizes the failure of Swartz to mention the prominent roles played by Tony Campolo and John Perkins in the prominence of the evangelical left.